2006
DOI: 10.1002/ccd.20914
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid alternative for high risk left main disease

Abstract: Percutaneous revascularization strategies for bifurcation disease of the left main are complex and carry significant risk. These risks are magnified in the setting of a left main which trifurcates. In a patient with complex ostial disease of two of the three limbs of a left main trifurcation, turned down for conventional bypass surgery, we report on a hybrid approach for complete revascularization, consisting of minimally invasive bypass grafting of the LAD combined with simultaneous drug eluting stent placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…There are, however, several successful examples including surgical valve replacement combined with percutaneous coronary intervention, 11 hybrid coronary revascularization, 12 and an apical minimally invasive surgical approach to "percutaneous" aortic valve implant currently under investigation. 13 In our patient, two infrequently used procedures from different disciplines were combined sequentially to provide effective treatment for a patient with otherwise inoperable end-stage aortic stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…There are, however, several successful examples including surgical valve replacement combined with percutaneous coronary intervention, 11 hybrid coronary revascularization, 12 and an apical minimally invasive surgical approach to "percutaneous" aortic valve implant currently under investigation. 13 In our patient, two infrequently used procedures from different disciplines were combined sequentially to provide effective treatment for a patient with otherwise inoperable end-stage aortic stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…HCR represents a “best of both worlds” strategy combining the long‐term survival advantage of a LIMA‐LAD bypass and PCI with DES to non‐LAD targets [22]. The LIMA‐LAD graft bypasses not only the current LAD stenoses but also future lesions that may develop in the atherosclerosis‐prone proximal LAD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Short‐ and mid‐term outcomes of mortality and morbidity have been favorably demonstrated . Several recent studies have shown comparable mortality, patency and incidences of major adverse cardiac event (MACE) rates when compared with conventional on‐ and off‐pump CABG surgery .…”
Section: Main Literature In Hybrid Coronary Revascularizationmentioning
confidence: 99%